APRIORI ALGORITHM FOR THE DETERMINATION OF THE GOODS SALES MARKET BANK - Fricles Ariwisanto Sianturi; Petti Indrayati Sijabat; Amran Sitohang; R. Mahdalena Simanjorang (Sean Institute, 2020)
Data mining a process of finding meaningful new relationships, patterns, and trends by filtering the huge data stored in the database using pattern recognition techniques. One of the data mining techniques is the a priori algorithm. A priori algorithm is defined as an algorithm for finding the highest frequency patterns. Currently, the a priori algorithm has been implemented in various fields, one of which is in the field of business or trade and the field of education. Market basket analysis technique or market basket analysis is a data mining technique that aims to find products that are often purchased simultaneously from transaction data. Bina Karya Swalayan is a modern market that has various types of goods. Where in the supermarket there are still some problems faced by a manager and employees